Pengembangan Sistem Manajemen Pendidikan Sosial untuk Pencegahan Perundungan di Lingkungan Sekolah - Mohzana; Jaelani Al-Pansori, Muh. (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This study aims to examine the development of a social education management system for bullying prevention at SMAN 1 Sikur, East Lombok. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving school principals, teachers, and students. The findings reveal that the implementation of social education in the school remains unsystematic and is not yet integrated into the school’s planning documents. The roles of teachers and school leaders in fostering an anti-bullying culture are still limited, and no internal policies explicitly support bullying prevention efforts. Nevertheless, there is significant potential to develop a culturally grounded social education system based on local wisdom from the Sasak community, such as the values of cooperation (begawe) and mutual assistance. Integrating these local values into the school’s social education management may enhance students' social character and foster a more inclusive and safe school environment. Therefore, a strategic, collaborative, and contextual management approach is needed to ensure sustainable bullying prevention initiatives.